Serpentine : an Alex Delaware novel - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels., 2021)
LAPD homicide lieutenant Milo Sturgis and brilliant psychologist Alex Delaware investigate a decades-unsolved case involving a rich and spoiled client, a mysterious birth mother and violent coincidences.